2021
DOI: 10.1007/s10443-021-09995-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Interfacial Properties of High-Modulus Carbon Fiber Reinforced PEKK Composites by a Two-Step Surface Treatment: Electrochemical Oxidation Followed by Thermoplastic Sizing

Abstract: A two-step surface treatment was conducted on high strength and high modulus carbon fibers (HSHM-CFs) to enhance the interfacial properties of polyetherketoneketone (PEKK) matrix composites. In the two-step surface treatment, the surfaces of HSHM-CFs were electrochemically oxidized followed by sizing treatment. Thermoset epoxy (EP) sizing agents and thermoplastic polyetherimide (PEI) sizing agents were utilized for comparison. Results showed that PEI sizing agents had better wetting effects than EP sizing agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
(108 reference statements)
0
3
0
Order By: Relevance
“…C1s spectra of CF/PEKK composites were resolved into four individual peaks at 284.40–285.13, 286.05–287.32, 288.99–291.53, and 292.95 eV, which correspond to CC/CH; CO; CO; and OCO, respectively. [ 34–36 ] After thermal conditioning, CO bond intensity increased while CO bond intensity decreased (Table 4). The CO (COH and COR) and OCO (COOH and COOR) bonds relate to the functionality of the surface, and the structural change is primarily characterized by CO bonds (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C1s spectra of CF/PEKK composites were resolved into four individual peaks at 284.40–285.13, 286.05–287.32, 288.99–291.53, and 292.95 eV, which correspond to CC/CH; CO; CO; and OCO, respectively. [ 34–36 ] After thermal conditioning, CO bond intensity increased while CO bond intensity decreased (Table 4). The CO (COH and COR) and OCO (COOH and COOR) bonds relate to the functionality of the surface, and the structural change is primarily characterized by CO bonds (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The high-resolution XPS spectra results are given in Figures 7 and 8 and Tables 4 and 5. The peaks at 284.43- [34][35][36] After thermal conditioning, C O bond intensity increased while C O bond intensity decreased (Table 4). The C O (C OH and C OR) and O C O (C OOH and C OOR) bonds relate to the functionality of the surface, and the structural change is primarily characterized by C O bonds (Figure 1).…”
Section: Physicochemical Changesmentioning
confidence: 99%
“…This method can produce relatively well-distributed oxygen-containing functional groups on the surface of carbon fibers and effectively improve the interfacial bonding strength of carbon fiber–resin matrix composites. Studies have shown that when the tensile modulus of a carbon fiber does not exceed 350 GPa, the graphitization degree of the carbon fiber surface is relatively low, and the effect of this surface treatment is better. Sun used ammonium bicarbonate as the electrolyte to continuously anodize the T300-grade carbon fiber, and the interfacial shear strength (IFSS) between the carbon fiber and the resin matrix increased to about 80 MPa.…”
Section: Introductionmentioning
confidence: 99%